Tindak Tutur Direktif pada Naskah Drama Nyonya-Nyonya Karya Wisran Hadi - Allyssa Ramadhani; Naila Sarwahita; Refa Amelia Putri; Aufannida Rahmalika Salsa Billa Azizia; Rina Mayaningsih; Agustin Kusumawardani; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines directive speech acts in the drama script Nyonya-Nyonya by Wisran Hadi, aiming to describe their forms and functions within the characters’ dialogues. The research focuses on the significance of understanding language functions in social and literary contexts, where directive speech acts reflect power relations, cultural values, and social dynamics among female characters. The study employs a pragmatic approach with a qualitative descriptive method. Data were collected through documentation and note-taking techniques on the drama script and analyzed using a pragmatic equivalent method to interpret utterances based on the context of the speaker, interlocutor, and situation. The results indicate 92 instances of directive speech acts divided into eleven categories: requesting, ordering, demanding, challenging, commanding, urging, coercing, forbidding, signaling, advising, and suggesting. These utterances demonstrate how language functions as a tool of social control, an expression of authority, and a reflection of moral values within society. This research enriches the field of literary pragmatics and provides practical contributions to Indonesian language education, particularly in understanding language functions in social interaction and literary works.